The Effectiveness of Guided Inquiry Learning Model with Digital Simulations to Enhance Students’ Critical Thinking Skills in Physics - Mahdalysa Dayu; Rahmatta Thoriq Lintangesukmanjaya; Lindsay N. Bergsma (Universitas Negeri Surabaya, 2025)
Objective: This study aims to determine the effectiveness of the guided inquiry learning model integrated with digital simulation in enhancing students’ critical thinking skills on the topic of harmonic oscillation. Method: A quasi-experimental method with a pretest-posttest control group design. The participants were two Grade XI classes at SMAN 1 Pacet: the experimental group received guided inquiry learning with digital simulations, while the control group received guided inquiry learning without simulations. Instruments used included critical thinking skill tests (pre-test and post-test), classroom implementation observation sheets, and student response questionnaires. Results: The results showed that the implementation of learning in the experimental class was in the “outstanding” category, with an average score of 3.62 (89.5%). The paired t-test analysis indicated a significant improvement between pre-test and post-test scores in both the experimental (p=0.000) and control (p=0.003) classes, with mean score differences of 32.90 and 20.20, respectively. The N-Gain value of the experimental class was 0.68 (medium category), which was higher than the control class’s N-Gain of 0.39 (medium category). Student responses toward the learning approach were highly positive, with an overall average 0f 82% in the “outstanding” category. Novelty: This study highlights the novelty of integrating PhET digital simulations into guided inquiry learning to foster critical thinking in physics education, specifically in understanding harmonic oscillation.